NCOG-18. OVERALL SURVIVAL VARIATION DUE TO THE TIMING OF POST-SURGICAL RADIATION IN HIGH-GRADE GLIOMAS. (14th November 2022) - Lowman, Allison; Bobholz, Samuel; Duenweg, Savannah; Kyereme, Fitzgerald; Cochran, Elizabeth; Coss, Dylan; Connelly, Jennifer; Mueller, Wade; Agarwal, Mohit; Banerjee, Anjishnu; LaViolette, Peter
Abstract: PURPOSE: Grade III and IV astrocytomas and glioblastomas are recognized as high-grade gliomas with aggressive heterogenous natures that carry with them a low overall survival (OS). Standard treatment currently involves surgical resection followed by radiation (RT) and concomitant chemotherapy. Despite this standard pathway, there is often disagreement in the optimal timing of radiation initiation post-surgery. In this study, we examined a subset of patients diagnosed with primary high-grade gliomas that underwent radiation following surgery at varying time frames. METHODS: 53 patients from our brain cancer bank with surgical diagnosis of high-grade gliomas were retrospectively analyses for this study. All patients were grouped into three cohorts based on the timing of the initiation of radiation post-surgery. Group 1 RT < 4 weeks, Group 2 RT 4-5 weeks, and Group 3 RT > 5 weeks post-surgery. Overall survival was calculated in days from initial surgical resection to time of death. RESULTS: Across the three patient cohorts, Group 1 included 9 patients (mean OS 430 days), Group 2 had 18 patients (mean OS 597 days), and Group 3 had 26 patients (mean OS 895 days). Overall survival trended towards a difference between the three radiation timing groups, with Group 3 showing better survival outcomes compared to Group 1 (p=0.07). CONCLUSIONS: This current study demonstrates a positive outcome with increased time between surgical intervention and initiation of radiation and concomitant chemotherapy. While we did not correct for additional treatment outside of standard clinical care, we would expect to observe similar trends. Despite these promising results for treatment planning, future research in larger cohorts is necessary to investigate possible molecular markers that may also impact treatment response and overall survival.